The Use of Appraisal and Debate Structure in English Debate Competition of Senior High School Students - Mardiana, Mardiana (Universitas Negeri Semarang, 2018)
This study aimed to explain the appraisal system manifested in students’ debate competition, the students’ realization of using appraisal, and the contribution of appraising items to debate structure. By using discourse analysis, the data which are in the form of transcripts from video recordings were analyzed in both tables of appraising items and debate structure. Several methods of analyzing data were done including transcribing, reading, categorizing, and analyzing. In order to validate the findings, the data and the analysis of this study had been examined and judged by one lecturer in West Nusa Tenggara as the expert of appraisal and debate. The findings map out the higher use of appreciation in attitude, disclaim in engagement, and force in graduation applied. The use of appreciation items makes students’ speeches more appreciative than personal and emotional. While a high occurrence of disclaim is applied for denying the debaters’ arguments from the opponent team, and the use of force of graduation is to express meaning when describing the situation or complaining about the statements and build up persuasion by assessing the degree of intensity of qualities and processes. Furthermore, the appraising items are more realized when students were doing rejection by using the low degree of gradability. Those appraising items are also highly found in both substantive arguments and rebuttal as the longer parts for explaining the substantial points in the debate competition.